Occupational Accidents among Hospital Staff - Pouran Raeissi; Amir Omrani; Omid Khosravizadeh; Masoud Mousavi; Edris Kakemam; Mobin Sokhanvar; Behnam Najafi (Iran University of Medical Sciences, 2015)
Background: The importance of safety in hospitals can be studied from different angles since hospital is a critical environment for incidents. Assessment of occupational accidents in hospitals can prevent their recurrence and maintain human and financial resources. This study aimed to investigate the occupational accidents among staff in a hospital.  Methods: This cross-sectional descriptive-analytical study was carried out in a hospital in Tehran University of Medical Sciences. Two hundred and thirty staff from various wards of the hospital were recruited by stratified random sampling. Data collection was performed using a researchermade questionnaire. Data were analyzed by the SPSS-20 software with descriptive statistics, Mann-Whitney and Kruskal-Wallis tests.  Results: The study results revealed that among staff, most of the occupational accidents was related to skin contact with blood or other body fluids and least of them belonged to toxicity with solvents. The results showed significant differences regarding occupational accidents between different groups of gender, years of work experience, organizational position, shift type, and age.  Conclusion: Since most of the occupational accidents happened at least one time among hospital staff, paying attention to prevention of it is necessary. Due to the complex nature of hospitals, management and prevention of occupational accidents require all personnel's willpower and involvement, and hospital management reform.